An Ethnomathematics Study on Weaving Activities and Their Integration into Mathematics Learning in Lailanjang Village, East Sumba Regency - Petronela Loda Atandima; Wara Sabon Dominikus; Aleksius Madu (JPMI (Jurnal Pendidikan Matematika Indonesia), 2026)
There are many Sumbanese, especially in Lailanjang Village, who engage in weaving activities, but they do not have a higher education. However, they are able to apply mathematical concepts in every weaving activity. In fact, if the community understands and is aware of it, weaving activities can be used as a culture-based mathematics learning activity that certainly has a beneficial influence in the world of education, especially in mathematics education. Ethnomathematics as a study of mathematical aspects related to culture, ethnomathematics comparatively studies mathematical practices from various human cultures. In the weaving activities carried out by the community in Lailanjang Village, many activities apply mathematical concepts ranging from how to design tools and equipment as a means for weaving, determining weaving time, calculating woven results, management to sales activities of weaving results. This study aims to describe ethnomathematics in weaving activities in Lailanjang Village, and related mathematical concepts and design learning tools for the mathematical concepts found. This research was conducted in East Sumba Regency, with four research subjects. The type of research is exploratory qualitative with an exploratory design. The researcher as the main instrument plays a role in collecting data through interview methods, observation, and documentation. Data validity uses source triangulation techniques. The results of the study indicate that there are values contained in weaving activities, namely social and kinship values, cultural and identity values, aesthetic values, religious or spiritual values, educational values, and economic values. Ethnomathematics in weaving activities in Lailanjang Village, Rindi District, East Sumba Regency includes the activities of calculating, measuring, localizing, designing, and explaining. From these activities, mathematical concepts can be identified. Mathematical concepts in Weaving Activities include the concepts of addition, multiplication, social arithmetic, measurement, geometry, and geometric transformation. Thus, these various mathematical concepts can be developed by designing learning tools. In this study, the concepts of geometric transformation (reflection) and social arithmetic were chosen to be designed as examples of mathematics learning tools in schools.Studi Etnomatematika pada Aktivitas Menenun dan Integrasinya dalam Pembelajaran Matematika di Desa Lailanjang, Kabupaten Sumba TimurABSTRAKTerdapat banyak warga sumba khususnya di Desa Lailanjang yang melakukan aktivitas menenun tetapi mereka tidak memiliki pendidikan yang tinggi, namun mereka mampu menerapkan konsep matematika di setiap aktivitas menenun. Padahal apabila masyarakat mengerti dan menyadarinya, aktivitas menenun dapat dijadikan aktivitas pembelajaran matematika berbasis budaya yang tentunya memberikan pengaruh yang bermanfaat dalam dunia pendidikan khususnya dalam pendidikan matematika. Etnomatematika sebagai kajian terhadap aspek-aspek matematika yang terkait dengan budaya, etnomatematika mempelajari secara komparatif praktik-praktik matematika dari berbagai budaya manusia. Dalam kegiatan menenun yang dijalankan masyarakat di Desa Lailanjang, banyak dalam aktivitasnya menerapkan konsep matematika mulai dari cara mendesain alat dan perlengkapan sebagai sarana untuk menenun, penentuan waktu menenun, menghitung hasil yang ditenun, pengelolaan hingga aktivitas penjualan hasil menenun. Penelitian ini bertujuan untuk mendeskripsikan etnomatematika pada aktivitas menenun di Desa Lailanjang, dan konsep matematika terkait serta merancang perangkat pembelajaran untuk konsep matematika yang ditemukan. Penelitian ini dilakukan di Kabupaten Sumba Timur, dengan subjek penelitian sebanyak empat orang. Jenis penelitiannnya kualitatif eksploratif dengan desain eksploratif. Peneliti sebagai instrumen utama berperan mengumpulkan data melalui metode wawancara, observasi, dan dokumentasi. Keabsahan data menggunakan teknik triangulasi sumber. Hasil penelitian menunjukkan bahwa terdapat nilai-nilai yang terkandung dalam aktivitas menenun yaitu nilai sosial dan kekerabatan, nilai budaya dan identitas, nilai estetika, nilai keagaman atau spiritual, nilai pendidikan dan nilai ekonomi. Etnomatematika pada aktivitas menenun di Desa Lailanjang, Kecamatan Rindi, Kabupaten Sumba Timur meliputi aktivitas menghitung, mengukur, melokalisir, merancang dan  menjelaskan. Dari aktivitas-aktivitas tersebut maka dapat diidentifikasi konsep- konsep matematika di dalamnya. Konsep matematika dalam Aktivitas Menenun meliputi konsep penjumlahan, perkalian, aritmatika sosial, pengukuran, geometri, dan transformasi geometri. Dengan demikian, berbagai konsep matematika ini dapat dikembangkan dengan merancang perangkat pembelajaran. Pada penelitian ini konsep transformasi geometri (refleksi) dan arimatika sosial dipilih untuk dirancang menjadi salah satu contoh perangkat pembelajaran matematika di Sekolah.Kata Kunci :Aktivitas Menenun; Nilai-nilai; Etnomatematika; Konsep Matematika; Pembelajaran Matematika